Pencapaian Jurusan Sejarah Universitas Negeri Padang (1999-2018) - Ryan Putra Utama; Mestika Zed; Aisiah Aisiah (Galanggang Sejarah, 2019)
This study examines the history of the Department of History in the era Universitas Negeri Padang (UNP) 1999-2018. During the journey of the Department of History in the UNP era, there was no writing about the Department of History. This study focuses on the achievement of the Department of History per period. The Department of History in the UNP era has been going on for five periods, under the leadership of Drs. Zafri, M.Pd, Drs. Bustamam, Hendra Naldi, S.S, M.Hum, and Dr. Erniwati, M.Hum. This study aims to describe the progress of the Department of History in the UNP Era. The research method used is the historical research methods. The results of this study, each period has different achievements, the meaning there are plus and minus. The leadership period of Drs. Zafri, M.Pd. The Department of History experienced development, especially in terms of means of supporting historical teaching. The Department of History has a Diorama, a Diachronic management room, and a library. Leadership Drs. Bustamam carved historical record, which was a conference and the International Workshop for the first time and not repeated until now. Leadership Hendra Naldi, SS, M.Hum was an improvement in the field of administration, the Department of History began to have good governance. Leadership Dr. Errniwati, M.Hum is an ongoing period. The achievement is the Department of History obtains accreditation A.